The making of a regional dictionary: Defining the process - Davey, William; MacKinnon, Richard (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2008)
Following the example of the two Atlantic regional dictionaries already published, the Dictionary of Newfoundland English Second Edition with Supplement (1990) and the Dictionary of Prince Edward Island English (1988), the co-editors, William Davey and Richard MacKinnon, began work on our ongoing project to create a dictionary of Cape Breton English in 1993. A pilot study determined that there were indeed enough words and senses that were original to Cape Breton or distinctive and characteristic of the variety of English used on Cape Breton Island, and our long-term project began. This paper discusses some of the interesting and absorbing decisions involved in creating a regional dictionary. After a brief consideration of how regional words differ from those in other varieties of English and how the words are collected, the focus shifts to the defining process we are currently using to write the “Dictionary of Cape Breton English”.